Lettice : A Christmas wish - Stanley, Mandy (London : HarperCollins Children's Books, 2010)
Lettice Rabbit peeps out of her burrow one morning to find her world covered in sparkly snow. Could this magical scene have something to do wit Christmas?. But What is Christmas? Lettice just has to find out..
K-3.
Keywords: Christmas -- Fiction; Snow -- Fiction